1998
DOI: 10.1007/s11745-998-0218-6
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and structural characterization of triacylglycerol lipase from Penicillium cyclopium

Abstract: An extracellular lipase, active on water-insoluble triacylglycerols, has been isolated from Penicillium cyclopium. The purified enzyme has a molecular mass of 29 kDa by gel filtration and SDS-polyacrylamide gel electrophoresis. It hydrolyzes emulsions of tributyrin, trioctanoin, and olive oil at the same rate as pancreatic lipase and shows very low activity against partial acylglycerols (monooctanoin and dioctanoin) and methyl esters. It is stable at 35 degrees C for 60 min and has maximal activity in a pH ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
16
2
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 39 publications
5
16
2
1
Order By: Relevance
“…The value obtained for P. solitum 194A was in line with the most well-known lipases from the genus Penicillium (a molecular mass in the range of 25-43 kDa), 29,34) similar to the value obtained for the type II lipases from P. camembertii (38 kDa) 5,35,36) and P. cyclopium (40-43 kDa). 5,35) Conversely, the value differed from the molecular mass of the type I P. solitum lipase previously reported (27 kDa). 5,35,37) This difference is likely to be due to an isoform of the enzyme secreted by this micro-organism.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The value obtained for P. solitum 194A was in line with the most well-known lipases from the genus Penicillium (a molecular mass in the range of 25-43 kDa), 29,34) similar to the value obtained for the type II lipases from P. camembertii (38 kDa) 5,35,36) and P. cyclopium (40-43 kDa). 5,35) Conversely, the value differed from the molecular mass of the type I P. solitum lipase previously reported (27 kDa). 5,35,37) This difference is likely to be due to an isoform of the enzyme secreted by this micro-organism.…”
Section: Discussionsupporting
confidence: 83%
“…5,35) Conversely, the value differed from the molecular mass of the type I P. solitum lipase previously reported (27 kDa). 5,35,37) This difference is likely to be due to an isoform of the enzyme secreted by this micro-organism. Evidence of an additional lipase secreted by P. solitum is noteworthy, because it supports the suggestion that penicillia are capable of producing more than one extracellular lipase.…”
Section: Discussioncontrasting
confidence: 56%
“…Em relação as cepas de Penicillium, vários trabalhos foram encontrados envolvendo produção, caracterização e purificação de lipases de diferentes espécies, como P. citrinum 36 , P. cyclopium 37 , P. simplicissimum 38 , P. caseicolum 39 , P restrictum 40 , P. expansum 41 , P. chrysogenum 42 , P. roqueforti 43 , P. camembertii 44 , P. abeanum 45 , entre outras espécies 46 . Entretanto, parece que este é o primeiro relato sobre a produção de lipase pelo fungo Penicillium solitum.…”
Section: Resultados E Discussão Produção Das Enzimas E Atividades Enzunclassified
“…Different microorganisms have been used for the production of lipases such as Rhizopus species, Rhizomucor mehei, Aspergillus niger, Penicillium species, Bacillus subtilus (12,13,14,25). Gopinath et al (9) reported about 34 wild fungal species associated with edible oil mill wastes which were isolated by the serial dilution technique.…”
Section: Introductionmentioning
confidence: 99%